Hoffbrand's essential haematology - Hoffbrand, A. V.; Steensma, David P.
"Essential Haematology is established as the most authoritative introduction to haematology. Beautifully presented, it introduces the formation and function of blood cells and diseases that arise from dysfunction and disruption of these processes. Basic science, diagnostic tests, clinical features and management are all clearly explained. The book outlines the basic principles of clinical and laboratory haematology and shows how manifestations of blood diseases can be explained by new knowledge of the disease processes"-- Provided by publisher